2020
DOI: 10.7717/peerj.10374
|View full text |Cite
|
Sign up to set email alerts
|

Wnt16 signaling promotes osteoblast differentiation of periosteal derived cells in vitro and in vivo

Abstract: Background Periosteum plays critical roles in de novo bone formation and fracture repair. Wnt16 has been regarded as a key regulator in periosteum bone formation. However, the role of Wnt16 in periosteum derived cells (PDCs) osteogenic differentiation remains unclear. The study goal is to uncover whether and how Wnt16 acts on the osteogenesis of PDCs. Methods We detected the variation of Wnt16 mRNA expression in PDCs, which were isolated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 30 publications
(43 reference statements)
2
10
0
Order By: Relevance
“…OPN is also a sign of early differentiation of osteoblasts, which can promote the reconstruction of mineralized tissues 40 . The level of COL‐I content and the osteogenic capacity of cells are complementary to each other and can be used as an important indicator of the differentiation ability of osteoblasts 41 . OC and BSP play a very important regulatory role in the process of cell mineralization and are mainly expressed in the later stages of osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OPN is also a sign of early differentiation of osteoblasts, which can promote the reconstruction of mineralized tissues 40 . The level of COL‐I content and the osteogenic capacity of cells are complementary to each other and can be used as an important indicator of the differentiation ability of osteoblasts 41 . OC and BSP play a very important regulatory role in the process of cell mineralization and are mainly expressed in the later stages of osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…40 The level of COL-I content and the osteogenic capacity of cells are complementary to each other and can be used as an important indicator of the differentiation ability of osteoblasts. 41 OC and BSP play a very important regulatory role in the process of cell mineralization and are mainly expressed in the later stages of osteoblasts. They are important indicators of osteoblast maturation and mineralization.…”
Section: The Mrna Expression Level Of Osteogenesisrelated Genesmentioning
confidence: 99%
“…Wergedal discovered that the periosteal bone formation rate and mineral apposition rate were reduced in Wnt16 knockout vs wild-type mice 31 . Ying Jin revealed that Wnt16 promotes osteoblast differentiation of periosteal-derived cells in vitro and in vivo with a potential application in improving bone regeneration 32 . Together, it is speculated Wnt16 signaling pathway can regulate ossification rather than chondrogenesis of antler.…”
Section: Discussionmentioning
confidence: 99%
“…Among these studies, two found that the overexpression of Wnt16 in osteoblasts or osteocytes primarily increased trabecular bone mass rather than cortical bone mass, suggesting that trabecular bone may be more sensitive to altered Wnt16 expression ( 58 , 59 ). In addition, in a mouse calvarial defect model, local transplantation of periosteal derived cells (PDCs), which were genetically engineered to express Wnt16, significantly increased trabecular bone volume/tissue volume and trabecular number ( 74 ). These findings are in consistent with human GWAS studies performed by different groups demonstrating the association between Wnt16 and spine/heel (predominantly trabecular bone) BMD ( 54 , 67 , 75 ).…”
Section: Regulation Of Bone Remodeling By Wnt16mentioning
confidence: 99%
“…Wnt16 is capable of inducing perivascular stem cell (PSC) proliferation and enhancing PSC differentiation towards osteoblasts in a c-Jun N-terminal kinase (JNK) pathway-dependent fashion ( 80 , 81 ). Similarly, Wnt16 promotes osteoblast differentiation from periosteal derived cells (PDCs) ( 74 ) as well as the differentiation of osteoblast progenitors into bone matrix-synthesizing osteoblasts by inhibiting canonical Wnt activity and upregulating Runx2 expression ( 82 ). However, it is worth noting that Wnt16 can also promote canonical Wnt activity to inhibit Runx2 expression and repress the differentiation of pre-osteoblasts ( 60 ).…”
Section: Regulation Of Bone Remodeling By Wnt16mentioning
confidence: 99%